Exploring individual foresight: Implications for organizational learning and innovation in firms - Melissa L Innes (Journal of Innovation & Knowledge (JIK), 2024)
Corporate foresight (CF) is considered an organizational capability that contributes to the innovativeness and sustained competitive advantage of firms, particularly in the presence of organizational learning (OL). The business literature positions individuals as important to the CF process but it provides limited clarification about how individuals do foresight or, more specifically, how they experience foresight in organizations. Embracing the resource-based view of the firm, this study provides understanding of how individuals use tacit knowledge in individual foresight (IF) and engage in OL mechanisms to contribute to innovativeness. The micro-foundations of IF are examined to determine how employees experience IF in an organizational context. Adopting a phenomenological approach, 27 interviews were conducted with employees across the finance and insurance and utilities industries, resulting in a theoretical framework of IF. Examining the lifeworld of individuals as they experience foresight revealed a rich tapestry of both personal and intra-organizational social capital interactions useful in demonstrating the role of IF for innovation in firms. Storytelling, mentorship, and group reflection, supported by appropriate culture, leadership, and human resource strategies, confirm the value of fostering IF to encourage innovation. This study advances foresight research by broadening understanding of IF from an employee perspective - specifically, how IF is experienced and can foster OL and innovation outcomes for firms. Implications for firms and opportunities for a future research agenda are proposed.
Keywords: D23; D83; O15; 650; Individual foresight; Organizational learning; Innovation; Knowledge management